2002
DOI: 10.1037/0278-6133.21.6.564
|View full text |Cite
|
Sign up to set email alerts
|

A brief assessment of concerns associated with genetic testing for cancer: The multidimensional impact of cancer risk assessment (MICRA) questionnaire.

Abstract: The Multidimensional Impact of Cancer Risk Assessment (MICRA) is a new tool to measure the specific impact of result disclosure after genetic testing. The authors compared its performance with that of questionnaires measuring general and cancer-specific distress. Participants (158 women) responded 1 month after they received genetic test results. The women were divided into 4 standard clinical test result groups: BRCA1/2 positive, BRCA1/2 negative, panel negative, and true negative. Factor analysis supported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
270
3
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(296 citation statements)
references
References 25 publications
16
270
3
7
Order By: Relevance
“…The Genetic Psychosocial Risk Instrument (GPRI) 125 is a validated, brief, and reliable 20-item instrument that screens for psychological risk among adults who are undergoing genetic testing for cancer and other adultonset hereditary diseases, but it is not specific to cancer. Three other instruments, the MICRA questionnaire, 92 the Genetic Risk Assessment Coping Evaluation (GRACE), 126 and the Psychosocial Aspects of Hereditary Cancer (PAHC) questionnaire, 127 more specific to the process of cancer genetic testing, as described in more detail below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Genetic Psychosocial Risk Instrument (GPRI) 125 is a validated, brief, and reliable 20-item instrument that screens for psychological risk among adults who are undergoing genetic testing for cancer and other adultonset hereditary diseases, but it is not specific to cancer. Three other instruments, the MICRA questionnaire, 92 the Genetic Risk Assessment Coping Evaluation (GRACE), 126 and the Psychosocial Aspects of Hereditary Cancer (PAHC) questionnaire, 127 more specific to the process of cancer genetic testing, as described in more detail below.…”
Section: Discussionmentioning
confidence: 99%
“…51 However, in some studies, an increase was observed in long-term distress among BRCA1/BRCA2 carriers. A 5-year prospective study by Graves et al demonstrated that women who were BRCA1/BRCA2 carriers reported greater genetic testing distress 91 measured according to the Multidimensional Impact of Cancer Risk Assessment (MICRA) questionnaire 92 regardless of their cancer status. The impact of the testing results on distress remained statistically significant after adjusting for receipt of riskreducing surgery.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 99%
“…To measure adherence, we used the validated 8-item Morisky medication adherence scale [22] at follow-up. To assess the psychological impact of the PGx test results at followup, several questions were adapted from the Multidimensional Impact of Cancer Risk Assessment questionnaire [23]; answer responses were 'never', 'rarely', 'sometimes' and 'often'. Newly developed questions specific to pharmaco genetics were also included to assess patients' experience and prior knowledge and perceived value of testing.…”
Section: Patient Surveysmentioning
confidence: 99%
“…Importantly, our results suggest that phenotype-genotype information could predict changes in both psychological well-being as well as general health. However, many have noted that measuring general mood or other psychological states may lack sensitivity to the important and unique issues that surround genetic testing, 17,18 or screening.…”
Section: Impact Of Hemochromatosis Screening On Well-beingmentioning
confidence: 99%